Ivabradine Ameliorates Kidney Fibrosis in L-NAME-Induced Hypertension - Stanko, Peter; Baka, Tomas; Repova, Kristina; Aziriova, Silvia; Krajcirovicova, Kristina; Barta, Andrej; Janega, Pavol; Adamcova, Michaela; Paulis, Ludovit; Simko, Fedor (Frontiers in Medicine, 2020)
Hypertension-induced renal injury is characterized by structural kidney alterations and function deterioration. Therapeutics for kidney protection are limited, thus novel renoprotectives in hypertension are being continuously sought out. Ivabradine, an inhibitor of the If current in the sinoatrial node reducing heart rate (HR), was shown to be of benefit in various cardiovascular pathologies. Yet, data regarding potential renoprotection by ivabradine in hypertension are sparse. Thirty-six adult male Wistar rats were divided into non-diseased controls and rats with L-NAME-induced hypertension to assess ivabradine’s site-specific effect on kidney fibrosis. After four weeks of treatment, L-NAME increased the average systolic blood pressure (SBP) (by 27%), decreased glomerular density (by 28%) and increased glomerular tuft area (by 44%). Moreover, L-NAME induced glomerular, tubulointerstitial and vascular/perivascular fibrosis by enhancing type I collagen volume (16-, 19- and 25-fold, respectively). Ivabradine decreased average SBP and HR (by 8% and 12%, respectively), increased glomerular density (by 57%) and reduced glomerular tuft area (by 30%). Importantly, ivabradine decreased type I collagen volume at all three of the investigated sites (by 33%, 38% and 72%, respectively) and enhanced vascular/perivascular type III collagen volume (by 67%). We conclude that ivabradine attenuated the alterations of glomerular density and tuft area and modified renal fibrosis in a site-specific manner in L-NAME-hypertension. It is suggested that ivabradine may be renoprotective in hypertensive kidney disease.